The value space: how firms facilitate value creation. Issue 4 (4th July 2016) - Lindman, Martti; Pennanen, Kyösti; Rothenstein, Jens; Scozzi, Barbara; Vincze, Zsuzsanna
Abstract : Purpose: – The purpose of this paper is to investigate the firm's role in the value creation process. In particular, after categorizing the activities that firms carry out to facilitate the creation of value, the "value space, " an actionable framework within which different dimensions of value creation are integrated, is developed and discussed. Design/methodology/approach: – The framework is built up on process theory, an in-depth review of the literature and a multiple case study carried out on 65 European firms in the furniture industry. Findings: – The value space is both a practical and theoretically based framework which contributes to the development of a more holistic and "actionable" view on the role of firm in the value creation process; also it provides managers with a tool to support the analysis, management and innovation of the value creation process. Originality/value: – The systematic categorization of firms' activities and their subsequent integration into a value creation framework are a missing piece in terms of understanding the value creation process carried out by firms. Also, by facilitating the analysis and innovation of the value creation process, the framework can be used to support both exploitative and explorative business process management.